EARLY DETECTION OF DEPRESSION IN CHILDREN AND ADOLESCENTS WITH CHRONIC DISEASE DURING THE COVID-19 PANDEMIC - Desy Wulandari; Wisnu Barlianto; Susanto Nugroho; Sony Wicaksono; Hajeng Wulandari (Caring : Jurnal Pengabdian Masyarakat, 2023)
Mental health in children and adolescents with chronic illnesses is still a problem that is rarely a concern in Indonesia. There are still many incidents of children and adolescents with depression due to the length of treatment they are undergoing, disease activity, psychological conditions, and support from the environment and family. Therefore, the detection of depressive disorders in children and adolescents still needs to be improved. The Covid-19 pandemic has made parents of patients afraid and anxious to bring their children to health facilities, so monitoring of mental health has been neglected, especially in pediatric and adolescent patients with chronic illnesses. This community service activity is aimed at providing counseling regarding the signs and symptoms of depression detection. Evaluation was carried out by filling out a questionnaire using the Children Depression Inventory (CDI). The conclusion from this activity is that 20% of children and adolescents with chronic illnesses experience mild depression, so further evaluation and intervention is needed.